ANALISIS PENERAPAN MEDIA PEMBELAJARAN RODA PUTAR VOLUME (RPV) DALAM MENYELESAIKAN MATERI VOLUME - Anisa; Fatimah, Fita; Khoerunisa, Intar; Wahyudi, Apri (JS (JURNAL SEKOLAH), 2024)
Abstract: The aim of this research is to analyze the application of the rotating volume wheel (RPV) learning media in completing volume material in elementary schools in Mathematics learning. descriptive and qualitative were used as methods in this research. Observations, interviews and literature reviews were used to collect research data. The data that will be analyzed uses test questions with 4 groups of students and the results show that students' ability to solve class V mathematical problems in elementary schools can be solved by using RPV media and using direct learning methods when learning mathematics. Thus, this lesson uses RPV media which is good for training students' problem-solving skills, especially in the volume of space material for class V students in elementary schools. Keyword: Learning Media For Rotating Volume Wheel (RPV), Geometric Volume, Mathematics Abstrak: Tujuan penelitian ini ialah menganalisis penerapan media pembelajaran roda putar volume (RPV) dalam menyelesaikan materi volume bangun ruang di sekolah dasar dalam pembelajaran Matematika. deskriptif dan kualitatif digunakan sebagai metode dalam penelitian ini. Observasi, wawancara, dan literatur review digunakan guna mengumpulkan data penelitian. Data yang akan di analisis menggunakan tes soal dengan 4 kelompok peserta didik dan hasilnya pada kemampuan peserta didik dalam memecahkan permasalahan matematis kelas V di sekolah dasar dapat teratasi dengan menggunakan media RPV serta melakukan metode pembelajaran secara langsung saat pembelajaran matematika. Dengan demikian pembelajaran ini menggunakan media RPV bagus untuk melatih kemampuan dalam memecahkan masalah peserta didik khususnya pada materi volume bangun ruang pada peserta didik kelas V di sekolah dasar. Kata Kunci: Media Pembelajaran Roda Putar Volume (RPV), Volume Bangun Ruang, Matematika